Analysis of Attendance System for Discipline Enforcement of Bappeda Fakfak Employees - Jamaluddin, Jamaluddin; La Alimuda, Risnayati; Isgunandar, Isgunandar (International Journal of Administration and Education, 2024)
The employee attendance system is a data collection on employee attendance which is part of the reporting activity in an agency in helping to improve order and discipline in the work environment. In Bappeda Fakfak, it was found that the attendance system in this office uses manual attendance. Previously, the Bappeda Fakfak office implemented a fingerprint attendance system or fingerprint machine but it did not last long, because the fingerprint machine or fingerprint machine was damaged so it returned to using the manual attendance system. found several employees who were less disciplined, this was proven by the fact that there were still employees who did not arrive on time according to office hours, besides that there were employees who only left their attendance because there were sudden activities so they could not directly fill in the attendance. This study aims to enforce discipline of Bappeda Fakfak employees. This study is qualitative, therefore, to achieve the objectives of the study, data collection techniques were used, namely observation, interviews, in this study there were 5 informants, namely the secretary of Bappeda Fakfak, the Head of the general and personnel sub-section, and 3 Bappeda Fakfak employees. Based on the results of this study, it shows that the discipline of Bappeda Fakfak employees is in the category of "quite Good. It can be seen from the indicators 1) Time compliance includes coming to work on time, namely every ASN employee or honorary employee of Bappeda Fakfak comes to the office at 07.30 and goes home at 15.30, although there are still some who come less than the office hours. Effective use of time, namely every employee manages time in various activities so that their performance is maximized. Never not working, namely every employee never does not carry out tasks at all, based on the results of research and interviews that in every activity must involve all colleagues and superiors so that the activities carried out run smoothly. 2) Responsibilities include obeying all orders, namely every employee carries out all regulations or guidelines in Bappeda Fakfak, then work targets, namely every Bappeda Fakfak employee has a target for every job they do, they must complete their work according to the deadline that has been set, and making daily work reports, namely all employees in Bappeda Fakfak make daily reports to evaluate the performance of employees concerned with the work or activities carried out recorded or written in the daily report based on their duties and functions.